Noble gases confirm plume-related mantle degassing beneath Southern Africa - S. M. V. Gilfillan (Nature Portfolio, 2019)
The elevation and high heat flow of Southern South Africa has controversially been attributed to a mantle plume. Here, the authors link degassed CO2 to a non-degassed mantle source rather than the convecting upper mantle, confirming plume-related mantle melting.